Human Resource Management in the 21st Century - มีทรัพย์ทอง, ชัชราวรรณ; คงคล้าย, จิราวรรณ; กิตติศักดิ์นาวิน, เฉลิมชัย (Business Administration and Management Journal Review, 2016)
Amid fierce competition Organizations need to adapt to survive and to become business leaders. Among all the resources that need to be used in the operation of that organization, human resource is the most valuable resource. And become the factors that make a business successful in operating or might defeat the competitors. For this reason, efficiency human resource management is very important in conditions of globalization. The purpose of this article is to describe the role and concept of human resource management. And the proposed guidelines for the management of human resources to succeed in the 21st century, in the view of scholars is proposed. Applicationto amend and improve the role of human resources in the organization to keep pace with the changes in current and in future.